Palau : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2009)
This report examines Palau's observance of Standards and Codes on the Financial Action Task Force's recommendations for antimoney laundering (AML) and combating the financing of terrorism (CFT). Palau has strengthened its AML/CFT legislative framework with the amendments to the Money Laundering and Proceeds of Crime Act of 2001 and the Financial Institutions Act of 2001, as well as the enactment of the Counter-Terrorism Act of 2007 and the Cash Courier Disclosure Act of 2007.